2015
DOI: 10.1007/s40519-015-0240-x
|View full text |Cite
|
Sign up to set email alerts
|

Seeking a perfect body look: feeding the pathogenic impact of shame?

Abstract: Shame feelings often lead individuals to adopt compensatory mechanisms, such as the minimization of the public display or disclosure of mistakes and the active promotion of perfect qualities, conceptualized as perfectionistic self-presentation. Although perfectionism is considered a central characteristic of disordered eating, the investigation on the specific domain of body image-related perfectionistic self-presentation and on its relationship with psychopathology is still scarce.The main aim of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Results showed that body image-related cognitive fusion was strongly associated with disordered eating severity, which is in line with previous research (Ferreira et al, 2014 ; Melo et al, 2019 ; Trindade & Ferreira, 2014 ). Moreover, confirming the results of previous empirical studies (Ferreira et al, 2016 ; Ferreira, Duarte, et al, 2018a ; Ferreira, Mendes, & Trindade, 2018b ; Ferreira, Ornelas, & Trindade, 2015a ; Ferreira, Trindade, et al, 2015b ; Marta-Simões & Ferreira, 2016 ), a strong relationship was found between body image-related perfectionist self-presentation and higher levels of disordered eating. Overall, these results corroborate previous studies that suggest that the entanglement with thoughts about body image and the need to exhibit a perfect body image to others, have a strong association with disordered eating attitudes and behaviours, and extend them by concluding that these relationships are also relevant in a sample of aesthetic athletic girls.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results showed that body image-related cognitive fusion was strongly associated with disordered eating severity, which is in line with previous research (Ferreira et al, 2014 ; Melo et al, 2019 ; Trindade & Ferreira, 2014 ). Moreover, confirming the results of previous empirical studies (Ferreira et al, 2016 ; Ferreira, Duarte, et al, 2018a ; Ferreira, Mendes, & Trindade, 2018b ; Ferreira, Ornelas, & Trindade, 2015a ; Ferreira, Trindade, et al, 2015b ; Marta-Simões & Ferreira, 2016 ), a strong relationship was found between body image-related perfectionist self-presentation and higher levels of disordered eating. Overall, these results corroborate previous studies that suggest that the entanglement with thoughts about body image and the need to exhibit a perfect body image to others, have a strong association with disordered eating attitudes and behaviours, and extend them by concluding that these relationships are also relevant in a sample of aesthetic athletic girls.…”
Section: Discussionsupporting
confidence: 88%
“…Since body image is an important issue in sports, especially in aesthetic sports, the need to present a perfect physical appearance seems to be particularly relevant in this context. According to Ferreira, Marta-Simões, and Trindade ( 2016 ), body image-related perfectionist self-presentation (defined as the need to present a perfect physical appearance to others) is positively linked with depressive symptomatology (Marta-Simões & Ferreira, 2016 ) and with disordered eating (Ferreira et al, 2016 ; Ferreira, Duarte, Pinto-Gouveia, & Lopes, 2018a , Ferreira, Mendes, & Trindade, 2018b ; Ferreira, Ornelas, & Trindade, 2015a , Ferreira, Trindade, Duarte, & Pinto-Gouveia, 2015b ). Nevertheless, body image-related perfectionist self-presentation remains unexplored in aesthetic athletes.…”
Section: Introductionmentioning
confidence: 99%
“…Although several researchers have reported associations between self-conscious emotions and depressive symptoms (see Kim et al, 2010, for a review), these reports are based on global measures of shame and guilt. This study is among the few that have assessed body-related self-conscious emotions (Castonguay et al, 2012(Castonguay et al, , 2014Conradt et al, 2007;Pila et al, 2015;Sabiston et al, 2010) and addresses calls to examine the link between body-related selfconscious emotions and health outcomes (Calogero and Pina, 2011;Marta-Simões and Ferreira, 2015). Specifically, these findings highlight that body-related self-conscious emotions are related to depressive symptoms and advance the current literature that is focused primarily on global self-conscious emotions (Averill et al, 2002;Gilbert, 2000;Webb, et al, 2007).…”
Section: Discussionmentioning
confidence: 58%
“…The relationship between shame and eating disorders (ED) has been known since early case descriptions of ED sufferers, and has been identified both in general populations and in clinical populations with ED [1][2][3][4]. In particular, most of the recent literature has focused on deepening the relationship between shame and appearance-related aspects of the disease, such as body dissatisfaction and the drive for thinness [5][6][7]. Moreover, some studies found patients with ED reporting higher levels of shame than a non-clinical sample [1,8].…”
Section: Introductionmentioning
confidence: 99%